2013
DOI: 10.1093/brain/awt315
|View full text |Cite
|
Sign up to set email alerts
|

Treatable childhood neuronopathy caused by mutations in riboflavin transporter RFVT2

Abstract: Childhood onset motor neuron diseases or neuronopathies are a clinically heterogeneous group of disorders. A particularly severe subgroup first described in 1894, and subsequently called Brown-Vialetto-Van Laere syndrome, is characterized by progressive pontobulbar palsy, sensorineural hearing loss and respiratory insufficiency. There has been no treatment for this progressive neurodegenerative disorder, which leads to respiratory failure and usually death during childhood. We recently reported the identificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
245
3
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(274 citation statements)
references
References 31 publications
(58 reference statements)
11
245
3
6
Order By: Relevance
“…Distinguishing the two entities at the molecular level is of high importance as patients with mutations in SLC52A2 can be ameliorated by riboflavin supplementation. 3 Furthermore, these two families illustrate the concept of spinocerebellar ataxia due to distinct mildly affected metabolic pathways, 1 as we demonstrate that partial loss of function in peroxisomes or mitochondria may lead to strikingly overlapping syndromes.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…Distinguishing the two entities at the molecular level is of high importance as patients with mutations in SLC52A2 can be ameliorated by riboflavin supplementation. 3 Furthermore, these two families illustrate the concept of spinocerebellar ataxia due to distinct mildly affected metabolic pathways, 1 as we demonstrate that partial loss of function in peroxisomes or mitochondria may lead to strikingly overlapping syndromes.…”
Section: Discussionmentioning
confidence: 63%
“…Recently, two studies have reported patients with p.(Gly306Arg) homozygous mutation and having not only sensorineural deafness and muscle weakness and wasting with respiratory insufficiency but also sensory ataxia and optic atrophy suggesting that mutations in SLC52A2 may be quite specific for the SCABD phenotype. 3,16 The published segregation of the disease with the 6p21-p23 chromosome interval in family A appears to be due to chance and not to linkage, as a LOD score of 3.25 corresponds to a probability of observing a false linkage of 0.05 after Bonferoni correction for multiple testing (whole-genome analysis). Correct linkage of the disease to 8qter was missed in this early study due to the high recombination rate of telomeric regions and to the absence of 8qter polymorphic markers in the initial Linkage Mapping Set used for whole-genome analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A salient example of how these advances can be immediately clinically relevant and affect treatment is provided by the genetics of the childhood-onset motor neuron disease, Brown-Vialetto-Van Laere syndrome. It was recently discovered via exome sequencing that mutations in riboflavin transport pathways are responsible for causing this disorder in a subset of patients [9]; this finding led to the identification of a novel mechanistic therapy (i.e., high-dose riboflavin) that seems to be effective for treating this previously intractable neurodegenerative disorder [10]. Another example of how sequencing approaches can be pertinent for an acquired disease is the recently reported use of sequencing for pathogen detection in a 14-year-old boy with severe combined immunodeficiency, who presented with meningoencephalitis [11].…”
Section: Introductionmentioning
confidence: 99%